Rehabilitation of people with severe mental disorder: A systematic review on the use of information technologies - Valero Aguayo, Luis; Ureña García, Angel (Revista Española de Comunicación en Salud, 2023)
Introduction: Severe mental disorder (SMD) is a growing health problem due to the increase in morbidity and mortality associated with it. The treatment of people with SMD includes the use of new technologies helping in the process of personal recovery. Objectives: To review and summarize the different types of interventions applied with SMD, and to determine their efficacy and quality. Method: A systematic review was carried out in the databases: Science Direct, Scopus, PsycLit, OT Seeker, Proquest, Dialnet and Scholar Google, and the quality of the studies found was assessed using the Downs and Black Checklist. Twenty-eight studies were included in the final review. Results: Most of them have been conducted on people with schizophrenia and other psychotic disorders, with moderate effect size. These studies have used computer-assisted therapy, mobile devices, video games, and virtual reality. Cognitive remediation therapy is the one that makes most use of technologies, with a significant improvement in cognitive behaviours. Conclusion: New technologies have potential to improve programmes for people with SMD. However, more, and better research with methodological quality is needed in order to accurately assess their implementation and efficacy.